Use of Escitalopram for pseudobulbar affect following severe traumatic brain injury: a case report - Malik, Muhammad Faisal Amir; Jafri, Mahmood Ali Khan; Asad Tamizuddin Nizami (Journal of the Pakistan Medical Association, 2023)
Those who have suffered from traumatic brain injury (TBI) often develop behavioural, affective, and cognitive complications. Some might experience episodes of involuntary and/or exaggerated laughter and crying. This condition is commonly known as ‘pseudobulbar affect’(PBA) and leads to anger, frustration, and social disability. This case report presents the use of low-dose Escitalopram in an individual suffering from agitation and PBA following severe TBI (sTBI). It emphasises the importance of adopting a holistic approach in the treatment of such individuals with appropriate attention paid to factors such as cognitive and behavioural impairment, and caregiver distress. Keywords: Traumatic brain injury, antidepressants, agitation, pseudobulbar affect, involuntary emotional expression disorder.